A Viral Double-Stranded RNA Up Regulates the Fungal Virulence of Nectria radicicola - II-Pyung Ahn; Yong-Hwan Lee (Molecular Plant-Microbe Interactions, 2001)
Double-stranded RNAs (dsRNAs) are widespread in plant pathogenic fungi, but their functions in fungal hosts remain mostly unclear, with a few exceptions. We analyzed dsRNAs from Nectria radicicola, the causal fungus of ginseng root rot. Four distinct sizes of dsRNAs, 6.0, 5.0, 2.5, and 1.5 kbp, were detected in 24 out of the 81 strains tested. Curing tests of individual dsRNAs suggested that the presence of 6.0-kbp dsRNA was associated with high levels of virulence, sporulation, laccase activity, and pigmentation in this fungus. The 6.0-kbp dsRNA-cured strains completely lost virulence-related phenotypes. This 6.0-kbp dsRNA was reintroduced by hyphal anastomosis to a dsRNA-cured strain marked with hygromycin resistance, which resulted in the restoration of virulence-related phenotypes. These results strongly suggest that 6.0-kbp dsRNA up regulates fungal virulence in N. radicicola. Sequencing of several cDNA clones derived from 6.0-kbp dsRNA revealed the presence of a RNA-dependent RNA polymerase (RDRP) gene. Phylogenetic analysis showed that this gene is closely related to those of plant cryptic viruses. Biochemical analyses suggested that the 6.0-kbp dsRNA may regulate fungal virulence through signal-transduction pathways involving cyclic AMP-dependent protein kinase and protein kinase C.